OPTIMIZATION OF THE USE OF SCANNING ELECTRON MICROSCOPY (SEM) EQUIPMENT IN THE CHEMICAL ENGINEERING DEPARTMENT OF LHOKSEUMAWE STATE POLYTECHNIC - Syafari, S (Jurnal Sains dan Teknologi Reaksi, 2024)
The purpose of this training is to optimize the use of chemical engineering laboratory equipment, namely Scanning Electro Microscopy (SEM), to improve the understanding and experience of students of the Lhokseumawe State Polytechnic, Department of Chemical Engineering. The methods used in this community service activity are intensive training, preparation of efficient usage protocols, and integration of SEM analysis results in research and teaching projects. At the end of this training activity, a question and answer session and assistance in the use of the tool were held to strengthen students' understanding of the training provided. Community service activities on optimizing the use of the Scanning Electro Microscopy (SEM) tool have been running well and optimally, and training participants stated that they were able to operate the tool and understand how to analyze samples using the Scanning Electro Microscopy (SEM) tool. Keywords:Laboratory,SEM,Chemistry,Optimization